Stabilitas vs. Efisiensi : Studi Komparatif Kinerja Keuangan Bank Syariah dan Konvensional di Indonesia - Firman Muhammad Abdurrohman Akbar (Jurnal Ekonomi Bisnis dan Akuntansi, 2024)
This study aims to comparatively analyze the financial performance of Islamic banks and conventional banks in Indonesia during the post-pandemic period (2021–2023). The research method applied is a comparative quantitative approach by examining five key financial ratios: CAR, NPL/NPF, ROA, ROE, and BOPO, using data from six major banks listed on the Indonesia Stock Exchange. Secondary data from annual financial reports were analyzed through descriptive statistics and an Independent Samples t-test. The results indicate significant differences in financial performance between Islamic and conventional banks across several ratios. In terms of capital adequacy (CAR), Islamic banks recorded an average of 30.15% compared to 24.95% for conventional banks, with t = -2.154 and sig. 0.045, reflecting stronger capitalization. Conversely, conventional banks outperformed in return on equity (ROE), averaging 19.50% compared to 12.85% for Islamic banks, with t = 3.122 and sig. 0.006, suggesting higher shareholder returns. Regarding operational efficiency (BOPO), conventional banks posted a lower average of 68.50% versus 76.90% for Islamic banks, with t = -2.890 and sig. 0.011, indicating better cost efficiency. Meanwhile, NPL/NPF (2.58% vs. 2.45%; sig. 0.442) and ROA (2.95% vs. 2.75%; sig. 0.687) showed no significant differences, implying comparable asset quality and profitability from assets in both groups. In conclusion, a trade-off between stability and efficiency emerges as the key distinguishing characteristic between the two banking systems